BIO ASSAY ANTIOKSIDASI EKSTRAK DAGING BUAH SALAK BONGKOK (Salacca edulis Reinw.) DENGAN KHAMIR Candida sp . Y390 - Dede Falahudin (Widyariset, 2010)
This research was conducted to determine antioxidant activity of Bongkok snake fruit crude extract by in vivo assay using yeast cell Candida sp.Y390 as experimental model. Crude extract has secondary metabolite compoundsuch as alkaloid, saponin, flavonoid, phenolic, and tannin. Mature crude extract of 200 ppm concentration potentially inhibits lipid peroxidase of yeast cell which has been treated by paracetamol 0.3%. The inhibitation ofthe 200 ppm extraxt concentration is higher than vitamin 0.225 mg/ml reaching 61.06% and 53.65% respectively.